Luchas estudiantiles en Bogotá 1980-1991 - Rey Hernández, Pilar Adriana (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
This research revolves around the central question: How to characterize the student struggles in Bogota during the years 1980-1991? In order to answer this question, the following three dimensions have been addressed: the general context of national education, the process itself of student struggles, and the referents for reconstruction and memory reproduction. The problem lies in the process by which, since the 1960s, as higher education expanded its access levels, student struggles showed a relative decline in their activity for internal reasons in the higher education system and in each university , But also for external reasons in relation to the social situation of the country. However, although their actions were less numerous with regard to numerable acts, on the other hand they were transformed into citizen expressions that are more distant from political parties and more concentrated in the field of culture and the practical social concerns of the Young people like working in popular neighborhoods. On the other hand, it is also necessary to recognize that the student organization during the study period presented less cohesion than in previous years, so it can not be categorized as a student movement specifically. However, it should be noted that more concerns began to appear on the scene to encourage creativity and the search to include the expressions of most of the student sectors, whether or not they have a particular militancy.

Esta investigación gira en torno a la pregunta central: ¿Cómo caracterizar a las luchas estudiantiles en Bogotá durante los años 1980-1991? Para poder dar respuesta a este cuestionamiento, se han abordado las siguientes tres dimensiones: el contexto general de la educación nacional, el proceso en sí de las luchas estudiantiles y los referentes de reconstrucción y reproducción memoria de las mismas. El problema se ubica en el proceso mediante el cual, desde los años sesenta, a medida que la educación superior fue ampliando sus niveles de acceso, las luchas estudiantiles presentaron un descenso relativo en su actividad por razones internas del sistema educativo superior y de cada universidad, pero también por motivos externos en relación con la situación social del país. Sin embargo, si bien sus acciones fueron menos cuantiosas en lo que respecta a actos numerables, por otro lado estas se fueron transformando en expresiones ciudadanas más alejadas de los partidos políticos y más concentradas en el ámbito de la cultura y las preocupaciones sociales prácticas de los jóvenes como el trabajo en barrios populares. Por otro lado, también es necesario reconocer que la organización estudiantil durante el periodo de estudio presentó menos cohesión que en años anteriores, por lo que no se la puede catalogar como movimiento estudiantil específicamente. Sin embargo hay que destacar que empezaron a aparecer en escena más preocupaciones por incentivar la creatividad y la búsqueda por incluir las expresiones de la mayor parte de los sectores estudiantiles, contaran o no estos con una militancia en particular.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; FH-M-2012-0034; Colombia; Liberación nacional; Fuerzas revolucionarias; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/264